Two Kinds of Topoi - Vasileva, Irina; Dvinyatin, Fedor; Stepanov, Andrej (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article deals with the classification of topoi and offers a distinction between conceptualizing topoi, based on similarity and juxtaposition or on the conceptual element of a rhetorical argument, and descriptive topoi, describing the world and the human being, which are close to formulae and cliches. The two kinds of topoi correspond to two fundamental categories of argumentation: “reflection” and “description”. The functions of these topoi are demonstrated on numerous examples from the literature of the post-rhetorical era (19th century), proving the continuity between this literature and the socalled “epoch of the ready-made word”.